The Crosstalk Between Saliva Bacteria and Fungi in Early Childhood Caries - Tu, Ye; Zhou, Zhiyan; Shu, Chang; Zhou, Yuan; Zhou, Xuedong (Frontiers in Cellular and Infection Microbiology, 2022)
Early childhood caries (ECC) is the most prevalent oral disease in children, which greatly affects the quality of life and health condition of the patients. Although co-infection of oral streptococci and fungi has been well recognized in the development of ECC, the correlation between other core members of oral mycobiome and ECC progression remains unclear. In the current study, saliva samples obtained from severe ECC (SECC), ECC, and caries-free children were collected, and both V3–V4 16S rRNA and ITS1 rRNA gene amplicon sequencing were performed to investigate the salivary bacterial and fungal profiles. Significant alteration of salivary fungal community in SECC/ECC children was observed compared with the caries-free control. The typing analysis determined the fungal community into five fungal types, which influenced the structure of salivary bacteria. By performing Spearman correlation analysis, carious phenotypes were positively related to Fusobacterium but negatively linked to Neocosmospora, and a significant correlation of cross-kingdom taxonomic pairs was identified. Our work demonstrated the interactions between oral bacteria and fungi at the community level, which may advance our knowledge on the etiological role of bacteria/fungi in the development of ECC and promote better management of this disease.